Research on the development law of freezing temperature field based on different refrigerant temperature. Issue 3 (May 2021) - Wang, Yue; Cui, Bingbing; Fu, Cai; Gao, Wei; Jiang, Haoliang
Abstract: In order to obtain the evolution law of freezing temperature field at different refrigerant temperatures, the mathematical model of freezing temperature field with phase transition in single tube was established, and the model test and numerical analysis were used to study it. The accuracy of numerical analysis is verified by comparing the data obtained by the two methods. Based on the numerical model, the development law of freezing temperature field under different refrigerant temperatures is analyzed by single factor analysis. The research results show that:(1) in silty clay formation, the development speed of frozen wall is about 26.67 mm/d under the condition of -27°C saline water freezing; (2) The refrigerant temperature has a great influence on the early development speed of the freezing wall. When the refrigerant temperature is between-50°C and-90°C, the time required to form a 0.8m freezing wall is advanced by 4 days for every 20°C decrease in refrigerant temperature. The research results provide reference for related practical projects.